The Hekima University College Chapel: A Brief Reflection (Hekima Review, 2015)
Space as an aspect of ordinary human experience and yet as potentially imbued with deep theological significance is rarely the subject matter of theological discourse. This brief reflection exposes how in the Hekima College chapel, space, art, and architecture are employed to communicate meaning bearing on the transcendent; theological significance simultaneously emerging from and emphasizing the Christian mysteries that are celebrated within this particular space in the city of Nairobi.